Risk Factors of Mortality in Severely-malnourished Children Hospitalized with Diarrhoea (Journal of Health, Population and Nutrition, 2011)
This case-control study was conducted in the Dhaka Hospital of ICDDR,B to identify the risk factors of mortality in severely-malnourished children hospitalized with diarrhoea. One hundred and three severelymalnourished children (weight-for-age